1990
DOI: 10.1002/polb.1990.090280503
|View full text |Cite
|
Sign up to set email alerts
|

Graft interpenetrating polymer networks of polyurethane and epoxy. I. mechanical behavior

Abstract: SUMMARYThe interpenetrating polymer networks (IPNs) prepared from polyurethane (PU) and a glycidyl ether of phenol formaldehyde (GEPF) were synthesized by using a simultaneous polymerization method. The effects of PU molecular weight and amount on the mechanical property are discussed. For the PU/GEPF IPNs based on polyester-type PU, as the PU content was increased, the tensile strength and fracture energy decreased, but the impact strength increased significantly. However, for the PU/GEPF IPNs based on pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 13 publications
2
57
0
3
Order By: Relevance
“…[11][12][13][14][15] Epoxy resin's properties have also been improved by using nanoparticles [16][17][18][19][20] as well as other cross-linkable polymers to form full-or semi-interpenetrating polymer networks. [21][22][23][24][25][26][27][28][29] Yilmazer and co-workers 16 have used unmodified montmorillonite (Cloisite Na + ) and organically modified Cloisite 30B as reinforcing agents for diglycidyl ether of bisphenol-A (DGEBA), Their results have shown an increase in the glass transition temperature (Tg) by more than 10°C with the addition of 9 wt% of a modified montmorillonite (MMT). The addition of 0.5 and 1 wt% of Cloisite 30B resulted in a maximum improvement in the impact strength of DGEBA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] Epoxy resin's properties have also been improved by using nanoparticles [16][17][18][19][20] as well as other cross-linkable polymers to form full-or semi-interpenetrating polymer networks. [21][22][23][24][25][26][27][28][29] Yilmazer and co-workers 16 have used unmodified montmorillonite (Cloisite Na + ) and organically modified Cloisite 30B as reinforcing agents for diglycidyl ether of bisphenol-A (DGEBA), Their results have shown an increase in the glass transition temperature (Tg) by more than 10°C with the addition of 9 wt% of a modified montmorillonite (MMT). The addition of 0.5 and 1 wt% of Cloisite 30B resulted in a maximum improvement in the impact strength of DGEBA.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane chains can be linked to the epoxy network through physical entanglements as well as chemical bonding to form graft interpenetrating polymer network (IPN) structures. Hsieh and Han 21 have evaluated the mechanical properties of graft IPN of an epoxy and a PUR based on polyols with different chain lengths. The results showed that the significant improvement in the tensile strength was related to the grafted structure and to the length of PUR chains.…”
Section: Introductionmentioning
confidence: 99%
“…In some respects the gelled blends of PBT and epoxy are similar to interpenetrating networks (IPNs) [37][38][39]. Semi-IPNs, in particular, are formed by mixing a monomer with a linear polymer and polymerizing the monomer around the polymer.…”
Section: Preparation Of Cured Pbt-epoxy Blendsmentioning
confidence: 99%
“…E-glass (electrical)-lower alkali content and stronger than A glass (alkali). Good tensile and compressive strength and stiffness, good electrical properties and relatively low cost [8][9]. Polymers are basically electrical insulators with low dielectric permittivity and often high dielectric strength.…”
Section: Introductionmentioning
confidence: 99%